2017 AHA/ACC Clinical Performance and Quality Measures for Adults With ST-Elevation and Non–ST-Elevation Myocardial Infarction: A Report of the American College of Cardiology/American Heart Association Task Force on Performance Measures. Issue 10 (October 2017) - Jneid, Hani; Addison, Daniel; Bhatt, Deepak L.; Fonarow, Gregg C.; Gokak, Sana; Grady, Kathleen L.; Green, Lee A.; Heidenreich, Paul A.; Ho, P. Michael; Jurgens, Corrine Y.; King, Marjorie L.; Kumbhani, Dharam J.; et al.
Abstract : Supplemental Digital Content is available in the text.